Circum-Antarctic Paleobathymetry to 30° South: Present to 75my ... - Hayes, Dennis; Weissel, Rose Anne; Zhang, C. (U.S. Antarctic Program (USAP) Data Center, 2025)
This software package models the paleobathymetry of the circum-Antarctic oceans back to the Late Cretaceous. It is based on a revised tectonic model of the circum-Antarctic region, and incorporates features such as spatially variable subsidence rates, refined rotation poles and a detailed treatment of selected areas. The software output consists of color-coded maps at user-specified Cenozoic ages and the associated gridded paleobathymetry for all oceans lying south of 30°S. This dataset was retrieved from NOAA NCEI (https://www.ncei.noaa.gov/products/circum-antarctic-paleobathymetry). Check https://www.ncei.noaa.gov/ ...